Police interrogations through the prism of science - Areh, Igor (Psihološka obzorja (Ljubljana), 2016)
Several approaches can be employed for information gathering from human sources, differing in their theoretical basis, goals, realisation, and ethical acceptability. The paper critically presents and compares two prevalent approaches to suspect interrogation used by the police. The older, prevalent interrogation approach focuses on obtaining suspects' incriminating statements and admissions, which severely elevates the risk of false confessions. Consequently, this interrogation approach is termed accusatorial or coercive since suspects are forced to admit to a crime. The newer interrogation approach is the information-gathering approach, also known as the investigative interview. It focuses on gathering accurate information in order to exclude or accuse a suspect in a criminal investigation. In comparison with coercive interrogation models, the information-gathering approach has a lower probability of false confessions since suspects are exposed to significantly lower levels of psychological pressure. Moreover, it is ethically more acceptable, has scientific grounds, enables the gathering of more accurate information, and has been found to be at least as ef fective as the coercive approach in criminal investigations. The investigative interview relies mainly on findings from social psychology. An analysis of coercive interrogation models reveals that they have no scientific basis and as such rely mainly on uncorroborat ed common-sense assumptions from authorities. In developed countries, coercive interrogation models are increasingly being replaced by the information-gathering approach, a trend connected with the enforcement of high human rights standards and a higher aware ness of risks associated with coercive interrogation methods by the general public, academia, and professionals alike.
Keywords: social psychology; socialna psihologija; interrogation; zasliševanja; police; policija; suspects; osumljenci; coercion; prisila; investigative interview; preiskovalni intervju